Harmony at home—nurturing work-pet family enrichment and harmony through a self-determination lens: The moderating role of the dark triad - Silva, D.; Junça Silva, A.; Pinheiro, P. (International Journal of Psychology, 2025)
Work-pet[family] enrichment has been recognised as an important part of the work-family boundaries as many families have pets of their own. Despite its increasing importance for both families and organisations, so far, no studies have explored how and when it increases harmony at home. Relying on the self-determination theory, we argued that work-pet[family] enrichment would improve employees' harmony through the satisfaction of autonomy, relatedness, and competency needs. It was also proposed that the Dark Triad (Machiavellianism, psychopathy, and narcissism) would moderate this indirect path. To test the proposed conceptual model, a daily diary study during 10 working days was conducted (67 × 10 = 670 measurement occasions). The multilevel findings supported the hypotheses and showed that work-pet[family] enrichment increased harmony through the satisfaction of the three psychological needs. Moreover, the indirect effect through competence and relatedness needs was moderated by the DT; however, the indirect effect of work-pet[family] enrichment on harmony through the satisfaction of autonomy needs was not moderated by the DT. Specifically, the relationship between work-pet[family] enrichment and harmony through relatedness and competency needs was stronger for those who scored higher on the DT. Practical implications are discussed.